Upaya Indonesia dalam Mendorong Prioritisasi Perekonomian Negara Berkembang melalui G20: Perspektif Hyper-Globalist - Imannulloh, Ervin Ramadhan; Rijal, Najamuddin Khairur (Indonesian Perspective, 2022)
This study aims to discuss the role of Indonesia in the G20 as a representative of developing countries in designing global economic policies with priorities for developing countries. In addition, this study examines Indonesia’s involvement in the G20 which has always been pro-active in drafting global economic policies. Furthermore, this article will discuss Indonesia’s strategic position in the 2022 G20 Presidency. This article also tries to prove that the cooperation carried out by countries in the world benefits all parties. This is a rebuttal to the skeptics’ statement that cooperation only benefits developed countries. The concept used in this research is the globalist concept using the neoliberal institutionalism theory. This article uses a descriptive method with literature study research techniques. The results of this study found that the designs of Indonesia’s economic policies in the G20 had a major impact on the sustainability of the economic growth of other developing countries. In addition, the results of this study will also prove that cooperation in the form of an international forum such as the G20 benefits all parties, as stated by the hyper-globalists.